2020
DOI: 10.1007/s00167-020-05999-2
|View full text |Cite
|
Sign up to set email alerts
|

The quadriceps insertion of the medial patellofemoral complex demonstrates the greatest anisometry through flexion

Abstract: PurposeA comprehensive understanding of the biomechanical properties of the medial patellofemoral complex (MPFC) is necessary when performing an MPFC reconstruction. How components of the MPFC change over the course of flexion can influence the surgeon’s choice of location for graft fixation along the extensor mechanism. The purpose of this study was to (1) determine native MPFC length changes throughout a 90° arc using an anatomically based attachment and using Schöttle’s point, and (2) compare native MPFC le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…However, different authors adopted different measures to properly mark them. For example, femoral attachment of MPFL was reported to be identified either by using Schöttle's point [25,27] or midway between adductor tubercle and medial epicondyle [14,23]. On the patellar attachment, authors reported identifying different insertions such as "at 20%, 40%, and 60% of the patellar length from the proximal tip" [22] or "20% (point 20), 30% (point 30), 40% (point 40), 50% (point 50), and 60% (point 60) from the superior pole of the patella" [25].…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, different authors adopted different measures to properly mark them. For example, femoral attachment of MPFL was reported to be identified either by using Schöttle's point [25,27] or midway between adductor tubercle and medial epicondyle [14,23]. On the patellar attachment, authors reported identifying different insertions such as "at 20%, 40%, and 60% of the patellar length from the proximal tip" [22] or "20% (point 20), 30% (point 30), 40% (point 40), 50% (point 50), and 60% (point 60) from the superior pole of the patella" [25].…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
“…From 10 original articles included in this review, nine studies identified multiple fibers of MPFL for assessment of length change [7,14,21,22,[24][25][26][27][28] and one study assessed only a single fiber [23]. Various femoral and patellar attachments were analyzed, as specified in Table 2.…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
See 3 more Smart Citations